PENGENALAN E-MARKET DALAM PENGEMBANGAN UMKM KRUPUK DI DESA TLASIH - Muhammad Miftachul Hidayat; Wahyu Eko Pujianto (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2023)
In today's relatively advanced era, the use of information media has a very crucial task. In matters of product promotion, we can use information media in the form of E-Market services as a means of promoting merchandise, this service can make the products we promote simple to find and be known by the wider community. The purpose of this community service is to increase Krupuk sales turnover by providing an introduction to the public about sales that can be carried out through E-Markets in the form of social media e-commerce. The method used is to hold direct deliberations with cracker entrepreneurs in Tlasih village and conduct structured training and mentoring. The impact of this dedication, cracker entrepreneurs can use and know the application of one of the E-Markets. It is hoped that this community service will be useful for many parties, both cracker entrepreneurs and SMEs in general.